AlGaN Channel High Electron Mobility Transistors with an AlxGa1−xN/GaN Composite Buffer Layer*Supported by the National Science and Technology Major Project of China under Grant No 2013ZX02308-002, and National Natural Science Foundation of China under Grant Nos 11435010 and 61474086. (July 2015) - Li, Xiang-Dong; Zhang, Jin-Cheng; Zou, Yu; Ma, Xue-Zhi; Liu, Chang; Zhang, Wei-Hang; Wen, Hui-Juan; Hao, Yue
<x content-type="archive" xml:space="preserve">Abstract</x> We report an AlGaN channel high electron mobility transistor (HEMT) on a sapphire substrate with a 1000-nm AlxGa1−xN (x = 0−0.18)/GaN composite buffer layer. With a significant improvement of crystal quality, the device features a high product of ns · μn. The AlGaN channel HEMTs presented show improved performance with respect to the conventional AlGaN channel HEMTs, including the on-resistance reduced from 31.2 to 8.1 Ω·mm, saturation drain current at 2 V gate bias promoted from 218 to 540 mA/mm, peak transconductance at 10 V drain bias promoted from 100 to a state-of-the-art value of 174 mS/mm, and reverse gate leakage current reduced from 1.85 × 10−3 to 2.15 × 10−5 mA/mm at VGD = −20 V.